2011
DOI: 10.1111/j.1743-498x.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Men’s health: it is imperative to teach scrotal and rectal examination

Abstract: If these results are confirmed by a larger study then consideration needs to be given to these programmes becoming a standard part of the curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…It is evident from this survey that they are underutilised in India. Alternatively, in addition to manikins, some educational institutes employ rectal teaching associates (RTAs), who are trained to help students learn DRE by allowing them to examine the RTAs’ own bodies . Students also need to be taught how to counsel patients on the need to undergo DRE in clinical situations to decrease the chance of the patient declining DRE.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident from this survey that they are underutilised in India. Alternatively, in addition to manikins, some educational institutes employ rectal teaching associates (RTAs), who are trained to help students learn DRE by allowing them to examine the RTAs’ own bodies . Students also need to be taught how to counsel patients on the need to undergo DRE in clinical situations to decrease the chance of the patient declining DRE.…”
Section: Discussionmentioning
confidence: 99%
“…These have been shown to reduce anxiety and improve both the students' comfort in clinical settings and their clinical expertise in performing the genitourinary examination. [3][4][5][6]8 This study found that Canadian medical students attending English-speaking programs are introduced to the urogenital physical examination in the first two years of their medical education. Preparatory resources, although available to students, vary wildly between schools.…”
Section: Discussionmentioning
confidence: 98%
“…Various approaches to support students through their initial experience with genital examinations have been found to successfully improve students' comfort and perceived ability. [3][4][5][6]8 The results of these studies, however, are based on questionnaires administered immediately before and after sessions specifically aimed to alleviate stress in an artificial environment, creating a huge bias. As students' focus is shifted to other areas of medical studies, their confidence in performing the urogenital examination diminishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also produce graduates who are better at handling the concerns and expectations their patients may bring to physical examination. The difficulty of teaching both the technical and interpersonal skills of physical examination has already been recognised to some extent in the use of clinical teaching associates in Australia and overseas for undergraduate and postgraduate teaching [29,30]. Mathewlynn et al [31] and Siwe et al [22] have suggested that clinical teaching associates are particularly helpful for male students who have been found to be more anxious about learning pelvic examination skills [20,32].…”
Section: Discussionmentioning
confidence: 99%